TRANSFORMASI PENCATATAN PELANGGARAN BERBASIS WEB: PROSES DAN IMPLIKASI TERHADAP KEDISIPLINAN PESERTA DIDIK - Nadhiva Qulba; Aidatum Muslimah; Moh. Dasuki (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to describe the transformation process of recording student violations from a manual system to a web-based application and to analyze its implications for student discipline at Madrasah Aliyah Negeri (MAN) 1 Jember. Method: This study employed a qualitative approach with a descriptive research design and a case study method. Data were collected through observations, semi-structured interviews, and documentation involving the principal, vice principals, discipline team members, guidance and counseling teachers, homeroom teachers, students, and parents. Results: The findings indicate that the transformation of the student violation recording system was driven by the ineffectiveness of the previous manual system, which resulted in delays in data recapitulation, repetitive administrative work, and limitations in real-time monitoring. As a solution, the madrasah developed a web-based application that enables student violations to be recorded directly, automatically, systematically, and transparently. The implementation of this application has improved the effectiveness of violation data management, facilitated monitoring processes, and strengthened student discipline through a point-based system that promotes self-awareness, responsibility, and self-regulation. Novelty: This study not only examines the technical implementation of a web-based student violation recording application but also explores the transformation process from a manual to a digital system and its implications for fostering a culture of discipline among students in the madrasah environment.